Students’ adaptive behaviors to Covid-19 impacts: A multidimensional analysis - Parreira, A.; Pestana, H.; Brandão, M.; Moutinho, L. (Ensaio: Avaliação e Políticas Públicas em Educação, 2023)
This investigation had three objectives: (i) to evaluate the impact of the Covid-19 pandemic on the emotional state and behavior of Higher Education students; (ii) to clarify the condition of students at the beginning of the pandemic; and (iii) to understand how they assess the impact and engage in adaptive behaviors. The sample involved 804 students in Brazil and Portugal. The results corroborate the hypotheses: the impact of the pandemic forced the emergence of energy dissipative structures; and student behavior stems not only from the negative emotional impact of Covid-19, but also from internal and external positive motivational factors. Online classes indicate three groups of students: enthusiasts, positive thinkers, and skeptics, with statistical differences between countries, gender, and professional status. The implementation of hybrid teaching should be considered to enhance student learning.